2011
DOI: 10.1080/13691058.2011.585405
|View full text |Cite
|
Sign up to set email alerts
|

Latina adolescents' perceptions of their male partners' influences on childbearing: findings from a qualitative study in California

Abstract: Teenage births among Latina women living in the USA remain higher than any other racial/ethnic group. This study explored the role that male partners play in the occurrence of pregnancy and their influence on teenage mothers' future plans in a sample of women pregnant with their first child. Qualitative analysis revealed that partners played a significant role in the use of contraception, timing and desire for pregnancy and young women's post-pregnancy plans for education, work and childrearing. Men's older ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Furthermore, racial-ethnic disparities persist, with disproportionately higher rates of pregnancy and birth among African American and Latina teenagers compared to Whites (Guttmacher Institute 2014). Although a significant proportion of teenage pregnancies are terminated, the birth rate among Latina teenagers remains the highest of all racial-ethnic groups and is twice that of non-Hispanic White teenagers (Braveman and Brindis 2011 Denner et al 2001;Gilliam 2007;Gilliam et al 2011;Minnis et al 2013;Schwartz et al 2011; for a substantive critique of the literature, see Geronimus 1997). Less attention has been paid to what happens during the time in between the discovery that one is pregnant and the decision to carry that pregnancy to term and become a parent.…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, racial-ethnic disparities persist, with disproportionately higher rates of pregnancy and birth among African American and Latina teenagers compared to Whites (Guttmacher Institute 2014). Although a significant proportion of teenage pregnancies are terminated, the birth rate among Latina teenagers remains the highest of all racial-ethnic groups and is twice that of non-Hispanic White teenagers (Braveman and Brindis 2011 Denner et al 2001;Gilliam 2007;Gilliam et al 2011;Minnis et al 2013;Schwartz et al 2011; for a substantive critique of the literature, see Geronimus 1997). Less attention has been paid to what happens during the time in between the discovery that one is pregnant and the decision to carry that pregnancy to term and become a parent.…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 95%
“…The social influence of parents -and especially mothers -and male partners impacts pregnant young women's decision not to place a child for adoption (Dworkin, Harding, and Schreiber 1993;Schwartz et al 2011). Daly (1994) found that adoption is not often regarded as a positive choice by families and peers of pregnant teenagers and for those interested in pursuing adoption, uncertainty about how to proceed inhibits them from resolving their pregnancies this way.…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…The procedure used here to explore family formation plans could be useful to address important aspects of adolescent pregnancy. This measure could also be explored in research from countries other than Mexico such as the U.S., where similar topics have been explored (Jumping-Eagle et al 2008;Plotnick 2007;Willoughby and Dworkin 2009) and where a large proportion of adolescent births are from Latina women (Schwartz et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Because of their possible relationship with pregnancy involvement and being pleased with a pregnancy among adolescent males, other variables included in the analysis were (1) being sporadically insured, given that sporadically insured children are more likely to have unmet medical needs and access barriers to care, including receipt of preventive care and having a usual source of care, where pregnancy-prevention discussions often occur (Olson, Tang, & Newacheck, 2005); (2) taking a virginity pledge, given that adolescents who take virginity pledges are less likely to use contraception and increasing the risk of pregnancy (Rosenbaum, 2009); (3) timing and source of sex education, given that these two factors are associated with adolescent pregnancy among females (Goldfarb et al, 1977); (4) accompanying a female partner to or receiving services at a family-planning clinic, given that adolescent males may be involved in pregnancy-prevention discussions during these visits, and obtaining contraception was the top reason for adolescent males to attend a family-planning clinic (Brindis et al, 1998); and (5) believing it is difficult to impregnate someone, given that concerns about fertility may cause adolescent males to not take an active role in pregnancy prevention with their female partners (Schwartz, Brindis, Ralph, & Biggs, 2011).…”
mentioning
confidence: 99%